Emergency physicians’ and nurses’ perception on the adequacy of emergency calls for nursing home residents: a non-interventional prospective study - Lemoyne, Sabine; Van Bastelaere, Joanne; Nackaerts, Sofie; Verdonck, Philip; Monsieurs, Koenraad; Schnaubelt, Sebastian (Frontiers in Medicine, 2024)
Introduction: A considerable percentage of emergency calls are for nursing home residents (NHR). Many of these interventions and hospital transfers are considered inappropriate. The study aimed to understand emergency physicians (EPs) and emergency nurses (ENs) perspectives on these calls and interventions and investigate factors contributing to their perception of inappropriateness. Methods: An exploratory non-interventional prospective study was conducted in Belgium among EPs and ENs. Electronic questionnaires were sent out in 2023. Results: A total of 114 emergency physicians and 78 nurses responded. Nursing home (NH) staff was perceived as understaffed and lacking in competence, impacting patient care especially during nights and weekends. General practitioners (GPs) were perceived as insufficiently involved in the patient’s care and often unavailable, leading to activation of EMS and transfers of NH residents to the ED. Advance directives were almost never available at EMS interventions and transfers were often not according with the patient’s wishes. Palliative care and pain treatment were perceived as insufficient. EPs and ENs felt mostly disappointed and frustrated. Differences in perception were noted between EPs and ENs regarding certain topics. ENs were more convinced that NH physicians should be available 24/7 and that transfers could be avoided if NH staff had more authority regarding medical interventions. ENs thought that pain management was inadequate, and EPs were more afraid of the medical implications of doing too little. Suggestions to reduce the number of EMS interventions were more GP involvement (82%), better NH staff education/competences (77%), more NH staff (67%), mobile palliative care support teams (65%) and mobile geriatric nursing intervention teams (52%). The appropriate EMS level was mostly not activated. Discussion: Physician staffed EMS interventions in NHs were almost never seen as necessary or indicated by EPs and ENs. Measures to address the shortages in numbers and competence of NH staff, insufficient primary care and absence of advance directives should be taken. GPs should be involved in the decision to call EMS and to transfer NHRs. Patients’ wishes should be respected. Better interprofessional communication, mobile geriatric and palliative care support teams are potential solutions. Structural improvements of the above-mentioned shortcomings are needed.